Complete genome sequence analysis of five russian rabies virus field isolates (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Five complete genomes of Russian rabies virus field isolates have been sequenced. These isolates were collected from different regions of European part of Russia. The genome lengths were 11923 nt (3 isolates), 11927 nt (1 isolate) and 11914 nt (1 isolate). All genomes retained basic genetic features characteristic for genotype 1 lyssaviruses. Four isolates were genetically close to European lineage of rabies virus and shared 93,4- 95,1% nucleotide identity with strain 9147FRA from France comparing complete genomes. One isolate from reindeer was genetically close to Arctic lineage of rabies virus and shared 99,7% nucleotide identity with strain A0906 from Alaska comparing gene N sequences. This is the first sequenced complete genome of Arctic lineage rabies virus. Furthermore to our knowledge this is the first proven case of Arctic lineage rabies virus distribution in Europe.